Ion transport studies on PMMA based polymer electrolytes / Ab Malik Marwan Ali, Dr. Muhd Zu Azhan Yahya and Dr. Ri Hanum Yahaya Subban - Ali, Ab Malik Marwan; Yahya, Muhd Zu Azhan (Dr.); Yahaya Subban, Ri Hanum (Dr.) (2006)
PMMA as the host polymer, lithium Imide ( LiN(CF3SC>2)2) as the doping salt, ethylene carbonate ( EC ) and propylene carbonate ( PC ) as the plasticizers was used in this present investigation. The PMMA salt complexes and plasticized PMMA salt complexes were prepared by solution casting technique. Electrical conductivity of all samples was measured using impedance spectroscopy technique at ambient and elevated temperature (303-383 K). The electrical conductivity of the samples was calculated using bulk resistant value which is obtained from the complex impedance plot in the frequency range from 100 Hz to 5 MHz. The electrical conductivity for pure PMMA is 1.6 x 10"8 S cm"1. The films containing 40 wt.% of LiN(CF3S02)2 exhibits the highest electrical conductivity with the value obtained is 2.3 x 10"6 Scm"1. This value is observed to increase for all samples with plasticizers. The temperature dependence studies show that the samples are ionic conductors and seem to obey the VTF rule. FTIR spectroscopy studies confirmed the polymer salt-interaction.